2008
DOI: 10.1007/s10562-008-9615-1
|View full text |Cite
|
Sign up to set email alerts
|

On the Formation of Pentylpiperidine in the Hydrodenitrogenation of Pyridine

Abstract: The hydrodenitrogenation of 2-methylpiperidine and 2-methylpyrrolidine was studied over sulfided NiMo/c-Al 2 O 3 in the presence of dialkylamines, alkylamines, and alkenes to determine why N-pentylpiperidine is formed in the hydrodenitrogenation of pyridine. N-alkylated 2-methylpiperidine and 2-methylpyrrolidine were only formed as primary products by reaction with alkylamines and not by reaction with 2-methylpiperidine and 2-methylpyrrolidine, or by reaction with an alkene. This indicates that, in the hydrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…3,13,[17][18][19] The calculations considered also Ni, Rh and Ir because a previous computational study showed that surfaces based on these metals displayed low to moderate activation energy barriers for dissociating the O-H in methanol. 28 These transition metals were used to design a working set of bimetallic catalyst surface models.…”
Section: Catalyst Surface Models and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,13,[17][18][19] The calculations considered also Ni, Rh and Ir because a previous computational study showed that surfaces based on these metals displayed low to moderate activation energy barriers for dissociating the O-H in methanol. 28 These transition metals were used to design a working set of bimetallic catalyst surface models.…”
Section: Catalyst Surface Models and Computational Detailsmentioning
confidence: 99%
“…14-16 Understandingly, several other bimetallic catalysts were investigated for hydrogen production; for instance, gold-and palladium based Au-Ru/ Fe 2 O 3 , Au-Cu/TiO 2 and Au-Pd/ZnO, 3,[17][18][19] or Pd-Cu/ZnAl 2 O 4 (ref. 20) bimetallic catalysts were found to reduce the formation of CO, CH 4 or coke byproducts.…”
mentioning
confidence: 99%
“…The HDN activity of Pt _ 1.5P catalyst little changed with higher reduction temperature. The order of maximum HDN activities of the NM _ 1.5P catalysts was Rh _ P Ru _ P Pd _ P Pt _ P. Since the aromatic C _ N bond is stronger than the aliphatic C _ N bond 45) , the removal of the nitrogen atom is carried out through hydrogenation of the aromatic structure and breaking of the resulting aliphatic C _ N bond 28),45), 46) . Thus, NiMo and NiW catalysts, which have higher hydrogenation activity than CoMo catalyst, are often used for the HDN reaction 45) .…”
Section: Hydrodenitrogenation Activities Of Noble Metalmentioning
confidence: 99%
“…Furthermore, since organic nitrogen compounds are well known to poison HDS catalyst 42) 45) , any high performance HDS catalyst should have high hydrodenitrogenation (HDN) activity. HDN of aromatic nitrogen compound occurs through hydrogenation of the aromatic ring, followed by cleavage of the C _ N bond to form NH3 and hydrocarbon 28),45), 46) . Therefore, high hydrogenation activity is one of the important characteristics of highly active HDS catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…2-Methylpyrrolidine and 2-methylpyrrole react with pentylamine to form N-alkylated compounds during the HDN of 2-methylpyrrolidine over NiMo/Al2O3 catalyst 18) . Other products with high selectivity were observed in the HDN of pyrrole over NiMoP/Al2O3 catalyst, as shown in Table 1.…”
Section: 2 Effect Of W/f On Catalytic Activity Formentioning
confidence: 99%